PSYCHOLOGICAL TRAINING OF SPECIALISTS IN THE FIELD OF PHYSICAL EDUCATION AND SPORTS: THEORETICAL ASPECTS AND PRACTICAL SIGNIFICANCE (Physical Culture and Sport: Scientific Perspective, 2025)
The article deals with the theoretical foundations of general and special psychological training of athletes as an important component of the sports training system. The main mental qualities formed in the process of psychological training, as well as methods of their development depending on the specifics of the sport are analyzed. The main sections of psychological training are characterized (general principles of psychological training of athletes, which combines the education of moral, volitional and other positive character traits; aspects of psychological training of athletes that reveal the level of achievements of athletes and their improvement (emotional sphere, motivational sphere, volitional sphere); methods of building a process of psychological training for establishing intrapersonal relationships; selection, orientation, control, forecasting and management in the system of psychological training. It is determined that psychological training is a process of development and improvement of significant manifestations of the athlete's psyche that meet the requirements of training and competitive activity (including the development of motivation, willpower, self-discipline, self-confidence, ability to self-regulate the psycho-emotional state, ability to manage attention, emotions and behavior in conditions of high stress) - is a complex and purposeful process of formation, development and improvement of mental qualities of a personality, which are necessary for achieving high results in physical education and sports, covering both general and special aspects of mental activity aimed at ensuring effective training and competitive activity. The four stages of psychological training (general psychological training, special pre-competitive psychological training, psychological training conducted directly during the competition, psychological training after the competition) are characterized. The implementation of the listed areas of psychological training of specialists in the field of physical education and sports requires preliminary planning, depending on the goals it is also divided into: operational, planning for a game or a specific competition; phased, planning is carried out for a month, stage or period of training camps; current for the annual cycle of training athletes; perspective for several years. Further research in the field of general and special psychological training of athletes should focus on the impact of psychological training on the long-term maintenance of motivation to play sports, prevention of burnout and adaptation of athletes during the transition between age or professional stages of their sports career. The perspective directions of improvement of psychological training with regard to modern scientific and methodological approaches are determined.
Keywords: psychological training; sport; general training; special training; mental qualities; competitive activity